Base-iodine-promoted metal-catalyst-free reactions of [60]fullerene with β-keto esters for the selective formation of [60]fullerene derivatives. Issue 41 (26th June 2020) - Yang, Han-Lin; Xu, Li-Jun; Li, Wen-Zhong; Sun, Tao; Duan, Bao-Rong; Chen, Si; Gao, Xiang
Abstract : In this study, methanofullerenes and 2′, 3′-dihydrofuran C60 derivatives were selectively synthesized in high yields via the reactions of C60 with β-keto esters under mild conditions by controlling the addition sequence and molar ratio of iodine and base. Abstract : In this study, methanofullerenes and 2′, 3′-dihydrofuran C60 derivatives were selectively synthesized in high yields via the reactions of C60 with β-keto esters under mild conditions by controlling the addition sequence and molar ratio of iodine and base. The structures of the products were determined by spectroscopic characterization. Moreover, a possible reaction mechanism for the selective formation of fullerene derivatives was proposed.